Enjoyment as a Predictor of Exercise Habit, Intention to Continue Exercising, and Exercise Frequency: The Intensity Traits Discrepancy Moderation Role - Teixeira, Diogo S.; Rodrigues, Filipe; Cid, Luis; Monteiro, Diogo (Frontiers in Psychology, 2022)
Given the need to explore the factors that can account for a better understanding of the intention-behavior gap in exercise practice in health club settings, and considering the emergence of hedonic assumptions related to exercise adherence, this cross-sectional study aimed to test the moderation effect of the intensity-traits agreement/disagreement in three relevant outcomes of exercise enjoyment: intention, habit, and exercise frequency. A sample consisted of 273 exercisers (male = 127; Mage = 36.21; SD = 11.29) enrolled in several health clubs (n = 9) fulfilled voluntarily a battery of questionnaires. All analyses were performed using SPSS v. 23.0/PROCESS v. 3.5. The results of the study presented a moderation effect of exercise intensity-traits agreement on three relevant enjoyment outcomes: exercise habit, intention to continue exercising, and exercise frequency. No relevant results emerged from intensity-traits disagreement. The results suggest that assessing and tailoring exercise prescription and supervision in order to customize exercise intensity may influence future exercise participation.